1997
DOI: 10.1038/sj.bjp.0701349
|View full text |Cite
|
Sign up to set email alerts
|

Renal vascular effects of the selective endothelin receptor antagonists in anaesthetized rats

Abstract: 1 Endothelin (ET) is a potent vasoconstrictor peptide which has been shown to have an important role in the regulation of systemic and renal haemodynamics. In order to elucidate the role of endogenous ET in the kidney, we examined the eects of ET receptor antagonists on systemic and renal vasculature in normotensive anaesthetized rats.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
41
0

Year Published

1999
1999
2012
2012

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 43 publications
(47 citation statements)
references
References 39 publications
6
41
0
Order By: Relevance
“…So far, few studies have investigated the effects of systemic inhibition of each step in the cascade of big ET/ET-1 cellular action on its renal function. 12,43,44 These studies do not allow for an unequivocal conclusion that ET B receptors coupled to NO synthesis are responsible for the diuretic and natriuretic actions of big ET-1 or locally produced ET-1. Therefore, the present study was carried out to test the involvement of the ET B receptor/NO axis in the renal and systemic actions of big ET-1.…”
mentioning
confidence: 96%
“…So far, few studies have investigated the effects of systemic inhibition of each step in the cascade of big ET/ET-1 cellular action on its renal function. 12,43,44 These studies do not allow for an unequivocal conclusion that ET B receptors coupled to NO synthesis are responsible for the diuretic and natriuretic actions of big ET-1 or locally produced ET-1. Therefore, the present study was carried out to test the involvement of the ET B receptor/NO axis in the renal and systemic actions of big ET-1.…”
mentioning
confidence: 96%
“…40 Acute administration of ET A receptor antagonists have little effect on renal and cardiovascular function in healthy normotensive animals, suggesting that ET does not exert a tonic influence on vascular resistance via the ET A receptor. 47,48 Information regarding the role of ET B receptors in regulating fluid volume balance has been obtained from studies using ET B receptor antagonists or rats and mice deficient in the ET B receptor gene. Gariepy et al have reported that rats deficient in a functional ET B receptor become hypertensive when given a high-salt diet.…”
Section: Et B Receptors In Hypertensionmentioning
confidence: 99%
“…Initial experimental evidence suggested that the constriction of the renal vasculature under physiological conditions was mediated by the ET B receptor given that (i) administration of the ET B receptor agonist sarafotoxin 6c induced a sustained renal vasoconstriction [9,35] and (ii) the constrictor activity of exogenously administered ET-1 could not be attenuated by ET A receptor blockade [9,36]. As pointed out by Matsuura et al [37], inhibition of endogenously produced ET is probably more physiologically relevant given their paracrine/autocrine mode of action. The administration of specific ET A antagonists under basal conditions has no effect on renal vascular tone [9,37,38] while ET B receptor blockade causes renal vasoconstriction [37,38] indicating that under physiological conditions in the rat ET reduces renal vascular tone via stimulation of the ET B receptor.…”
Section: Discussionmentioning
confidence: 83%
“…As pointed out by Matsuura et al [37], inhibition of endogenously produced ET is probably more physiologically relevant given their paracrine/autocrine mode of action. The administration of specific ET A antagonists under basal conditions has no effect on renal vascular tone [9,37,38] while ET B receptor blockade causes renal vasoconstriction [37,38] indicating that under physiological conditions in the rat ET reduces renal vascular tone via stimulation of the ET B receptor. Under pathophysiological conditions, changes in the expression of ET receptors in the kidney have been reported.…”
Section: Discussionmentioning
confidence: 99%